Rechargeable Batteries: Regulating Electronic and Ionic Transports for High Electrochemical Performance. Issue 5 (2nd December 2021) - Xu, Xiaolong; Zhao, Xiuxiu; Hui, Kwan San; Dinh, Duc Anh; Hui, Kwun Nam
Abstract: Rechargeable batteries are serving society and are continuing to develop according to application requirements. Recently, rechargeable batteries with high energy density, power density, stability, and rate performance, as well as low cost have attracted the attention of researchers globally. However, achieving all these merits in a single rechargeable battery system is difficult. Accordingly, many approaches are reported to improve the performance of different energy storage devices. Nevertheless, reports on a general research method to improve the performance of battery systems are still limited. Herein, the current progress of rechargeable batteries and the corresponding opportunities and challenges are summarized. The principles of electrochemical reactions for lead–acid batteries, metal–ion batteries, metal–sulfur batteries, and metal–air batteries are introduced and compared. The technological challenges in the development of rechargeable batteries on the basis of transports of electrons and ions are comprehensively analyzed. In particular, approaches for regulating electronic and ionic transports are comprehensively discussed for the enhancement of electrochemical performance. Some advanced energy storage materials with good electronic and ionic conductivities are also highlighted. Furthermore, several perspectives on potential research directions for the choice and design of high‐performance rechargeable batteries for practical application are proposed. Abstract : This review summarizes the current progress of various rechargeable batteries such as lead–acid batteries, metal‐ion batteries, metal–sulfur batteries, and metal–air and the corresponding opportunities and challenges. Approaches for regulating the electronic and ionic transports, including controlling phase transition, suppressing electrode active material orientation, introducing the electrocatalytic phase, and modifying the surface reactivity and electrode/electrolyte interface, are comprehensively discussed.